Development and validity of a short web-based semi-quantitative Food Frequency Questionnaire applicable in both clinical and research setting: an evolution over time - Verbeke, Joke; Boedt, Tessy; Matthys, Christophe (Frontiers in Nutrition, 2023)
Background: Assessing dietary intake is valuable both in clinical practice and in research. In research and in clinical practice the long-term habitual dietary intake is most often of interest. Therefore, a web-based semi-quantitative Food Frequency Questionnaire (FFQ) was developed to measure habitual intake of nutrients and foods. Aim: To assess content validity, convergent validity and reliability of a 32-item semi-quantitative FFQ for adults. Methods: Three different cohorts of Flemish adults were recruited in the past 10 years. A first cross-sectional validation study took place in 2013, consequently in 2019 and 2021. Content validity was assessed in 2019 through a semi-structured cognitive interview. Convergent validity was assessed by examining mean differences, Wilcoxon signed rank test, Spearman’s correlation coefficients (SCC) and Bland-Altman analysis for energy, nutrient and food group intake compared to a 3-day food record (FR). Additionally, consumers-only analysis was performed together with cross-classification analysis by assessing ranking capabilities of the FFQ into quartiles and weighted kappa. Reliability was assessed through evaluation of SCC and intra-class correlation (ICC) of test-retest assessment of the FFQ. Results: SCC for energy and absolute nutrient intake between the FFQ and the FR ranged from 0.02 to 0.54. Compared to absolute macronutrients, higher SCC were found for the majority of the relative macronutrient intake and most food groups. Bland-Altman plots showed improved agreement and decreasing bias between the FFQ and the FR over time. Misclassification of the FFQ for nutrients was acceptable and decreased over time (7.4%, 7.5% and 6.8% in 2013, 2019 and 2021 respectively) but weighted kappa’s remained mostly fair (κ ≤0.20). Reliability of the FFQ was good and improved over time (mean SCC of 0.65 and 0.66 p <0.001 in 2013 and 2019). Conclusion: The short web-based FFQ is an easy, low-cost and feasible tool with good reliability, low misclassification and acceptable validity to compare nutrient densities and food group intake on population level. Measurement of absolute intake remains debatable.